Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Parabola: Abdul Syukur Bahaman Naqib Harun Muhd Zaki Abd Bahari Mohd Musthaqim Shafiee

Download as ppt, pdf, or txt
Download as ppt, pdf, or txt
You are on page 1of 15

Parabola

Abdul Syukur Bahaman


Naqib Harun
Muhd Zaki Abd Bahari
Mohd Musthaqim Shafiee
Definition
a set that consists of all the points in a plane
equidistant from a given fixed point and a
given fixed line in the plane is a parabola. The
fixed point is the focus of the parabola. The
fixed line is the directrix
Standard-form equations for parabolas
with vertices at the origin (p>0)
EQUATION FOCUS DIRECTRIX AXIS OPENS
x = 4py (0,p) y = - p y-axis Upwards
x = - 4py (0,-p) y = p y-axis Downwards
y = 4px (p,0) x = - p x-axis To the right
y = - 4px (-p,0) x = p x-axis To the left
USING GSP
USING GSP
TAKEN FROM INTERNET
Adding to our diagram from above,
we see that the distance d = y + p.
Now, using the distance formula on
the general points (0, p) and (x, y), and
equating it to our value d = y + p, we
have
Squaring both sides gives:
(x 0)
2
+ (y p)
2
= (y + p)
2

Simplifying gives us the formula for a parabola:
x
2
= 4py
In more familiar form, with "y = " on the left, we
can write this as:

where p is the focal distance of the parabola.

Example - Parabola with Horizontal Axis
Sketch the curve and find the equation of the
parabola with focus (-2,0) and directrix x = 2.

After sketching, we can see that the equation
required is in the following form, since we
have a horizontal axis:
y
2
= 4px
Since p = -2 (from the question), we can
directly write the equation of the parabola:
y
2
= -8x

Shifting the Vertex of a Parabola from
the Origin

This is a similar concept to the case when we
shifted the centre of a circle from the origin.
To shift the vertex of a parabola from (0, 0) to
(h, k), each x in the equation becomes (x h)
and each y becomes (y k).
So if the axis of a parabola is vertical, and the
vertex is at (h, k), we have
(x h)
2
= 4p(y k)

If the axis of a parabola is horizontal, and the
vertex is at (h, k), the equation becomes
(y k)
2
= 4p(x h)

You might also like